Research and development of the identification/authentication complex in information systems - Ostapets, D. O.; Lapin, V. (Science and Transport Progress, 2008)
The identification / authentication subsystem architecture of information systems is considered; the analysis of their demerits is done. Advisability of using the onetime passwords generation systems is shown. The software complex of onetime passwords generation is described; the research of their characteristics (the time window and hardware requirements) is performed.